Pengaruh Konsentrasi Senyawa Dihidroksi Etilena Urea (Akrofik NZK) Pada Proses Finishing Kain Kapas 100% Dengan Metode Pemanas Awetan Suhu Rendah (Low Curing) Terhadap Stabilitas Dimensi, Kekuatan Sobek Dan Kekuatan Tarik - Luciana Laksmi; Riza Rizkiah (Sainteks: Jurnal Sain dan Teknik, 2020)
The process of producing uniforms or shirts made of 100% cotton which has a pattern of weaving or printing is very much in demand, especially in Indonesia with a tropical climate which is suitable for wearing clothes made from cotton. The need for 100% cotton fabric needs both domestically and abroad made the textile companies intensely innovate because of the connection with the quality of the cotton fabric to meet market standards and in accordance with consumer desires. There are several factors that usually affect the quality of a fabric, including dimensional stability, tensile strength and tensile strength. Anti-creasing enhancements are a form of resin refinement application intended to improve the wrinkle-resistant properties of cellulose fabrics. The purpose of this study was to determine the optimum conditions that can be achieved from the addition of anti-tangle resin substances (Acrylics NZK) to the physical properties of the fabric. The resin used was an anti-creasing resin with the trade name Ackfik NZK (Dihydroxy Ethylene Urea) using a temperature of low heating (Curing 130 C) and a concentration variation of 80, 90. 100,110 g / l. The results showed the optimum conditions achieved in this experiment were the concentration of anti-creasing agent 100g / l with a heating temperature of 130 C obtained a formaldehyde-free content of 55.80 ppm, dimensional stability of 3.2% wariness of 2.4% warp and towards the feed , tear strength of 0.640 kg of cloth towards the warp of 0.625 kg in the direction of feed, Pull strength of fabric 24.43 kg in the direction of warp 11.86 kg in the direction of feed.